Treatment of hysterical aphonia - j, Bharath Raj; Saraswathi Menon (Journal of All India Institute of Speech and Hearing, 1972)
Miss S, aged 15 years studying in VII standard reported at the Institute with a complaint of no speech. She came to the clinic with her father, brother and brother-in-law. She had four siblings and belonged to a middle class family. There was no family history of speech and hearing problems, and her development was known to be normal. She had developed this problem 4 days prior to coming to the clinic